MULTI LEVEL MARKETING SHARIA - Herry Syahbannuddin Nasution; Andri Soemitra (IAIN Lhokseumawe, 2022)
Sharia MLM Business is dependent business on standard sharia. Study this use method study literature study and approach descriptive qualitative that is content analysis of papers from the Google Scholar database. Selected paper in this review originated from search on the Google Scholar database with the keywords